Resilience and Self-Care in Patients with Heart Failure: A Cross-Sectional Study - Qasim Kani Hayef; Alice Khachian; Alaa Jawad Kadhim; Mahnaz Seyedoshohadaee; Shima Haqhani (Kufa Journal for Nursing Sciences)
Background: A key component of managing heart failure, self-care can significantly affect patient outcomes. Patients may find the constant and intricate demands of self-care stressful, and they may need to show resilience to manage their symptoms.